2013
DOI: 10.1016/j.vaccine.2012.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Prime-boost BCG vaccination with DNA vaccines based in β-defensin-2 and mycobacterial antigens ESAT6 or Ag85B improve protection in a tuberculosis experimental model

Abstract: The World Health Organization (WHO) has estimated that there are about 8 million new cases annually of active Tuberculosis (TB). Despite its irregular effectiveness (0–89%), the Bacillus Calmette-Guérin) BCG is the only vaccine available worldwide for prevention of TB; thus, the design is important of novel and more efficient vaccination strategies. Considering that β-defensin-2 is an antimicrobial peptide that induces dendritic cell maturation through the TLR-4 receptor and that both ESAT-6 and Ag85B are immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 44 publications
0
27
0
1
Order By: Relevance
“…These results suggested that BCG/ DNA vaccination might be a potential candidate since it was able to generate a much prolonged Th1 immune response when compared with BCG and BCG+ P groups. As many previous studies demonstrated a positive correlation between Th1 immune response and protection [15,50,51], we infer that the improved Th1 immune response elicited by the BCG prime/DNA boost strategy may result in a stronger protection than other groups in this study; however, it still needs to be confirmed by further studies. For future studies, we are planning to develop a viral-based vaccine and rBCG expressing Rv0577 protein, then use subunit vaccines to boost rBCG and to evaluate the protective efficacy and safety of this promising vaccines.…”
Section: Discussionmentioning
confidence: 48%
“…These results suggested that BCG/ DNA vaccination might be a potential candidate since it was able to generate a much prolonged Th1 immune response when compared with BCG and BCG+ P groups. As many previous studies demonstrated a positive correlation between Th1 immune response and protection [15,50,51], we infer that the improved Th1 immune response elicited by the BCG prime/DNA boost strategy may result in a stronger protection than other groups in this study; however, it still needs to be confirmed by further studies. For future studies, we are planning to develop a viral-based vaccine and rBCG expressing Rv0577 protein, then use subunit vaccines to boost rBCG and to evaluate the protective efficacy and safety of this promising vaccines.…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, any vaccines or vaccination strategies that are able to elicit the mucosal immune response may enhance the efficacy of protection against Mtb infection. Great efforts have been made to improve the protective efficacy of TB vaccines and various types of vaccine candidates or vectors have been developed, including the recombinant BCG (rBCG), DNA vaccines, nanoparticle vaccines, recombinant modified vaccinia virus Ankara and recombinant adenoviral-based vaccines (12,15,32,59,60). Among them, the adenoviral-based TB vaccines have gained increased attention, as they were first evaluated as mucosal TB vaccine candidates (15).…”
Section: Discussionmentioning
confidence: 99%
“…Such prime-boost vaccination strategies have demonstrated the potential to elicit protective immune responses, including (8)(9)(10)(11)(12). Mtb is an intracellular pathogen transmitted via a mucosal route; mucosal and cellular immunity have thus been suggested to have pivotal roles in protection against Mtb infection.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these results are also different from several other studies where cytokine levels were determined in lung homogenates from mice vaccinated and/or treated with different vaccine candidates (including Hsp65). In these studies the amounts of cytokines detected corresponds to the production of the whole resident lung cells and not only to T cells (e.g., Bonato et al, 8 Sable et al 47 and Cervantes-Villagrana 48 ). For these reasons, the data presented here is not possible to be directly compared with those from the studies recently mentioned.…”
Section: Discussionmentioning
confidence: 99%